Localization and Biosynthesis of Functional Thrombomodulin in Human Megakaryocytes and a Human Megakaryoblastic Cell Line (MEG-01) - Ogura, Michinori; Ito, Takahiko; Maruyama, Ikuro; Takamatsu, Junki; Yamamoto, Shuji; Ogawa, Kohei; Nagura, Hiroshi; Saito, Hidehiko (Thrombosis and Haemostasis, 1990)
The localization and biosynthesis of functiosnal thrombomodulin (TM) on the cell surfaces of human platelets, megakaryocytes and a human megakaryoblastic cell line (MEG-01) were investigated. TM was demonstrated on the cell surfaces and in cytoplasms of human platelets, megakaryocytes and MEG-01 by an indirect immunofluorescent technique using monospecific rabbit anti-human TM serum. Immunoelectronmicroscopic analysis revealed that TM was localized in plasma membranes of MEG-01 cells as well as human megakaryocytes. 125I-monoclonal antithrombomodulin IgG binding assay showed that one MEG-01 cell possessed approximately 78,000 TM molecules on its cell surface. Thrombin-dependent protein C activating-cofactor activity was demonstrated on MEG-01 cells. Northern hybridization technique using cDNA probe of TM revealed that poly(A)+-RNA from MEG-01 cells showed a single band of 3.8 kb similar to that from human endothelial cells. These data suggest that human megakaryocytes synthesize functional TM, and thereby platelets possess TM on their surfaces. TM on platelets may participate in the activation of protein C at the site of a hemostatic plug.